Going Parallel. - Rotman, Brian (Substance: A Review of Theory & Literary Criticism, 2000)
Discusses the ways in which a collective mind reverberates through the individual brain. Parallelism of the human mind; Growth of parallelist and visualist thinking within contemporary, technology-based culture; Discussion on human computing.